Integration of carbon nanotubes in silicon resonators - Duran-Valdeiglesias, E.; Zhang, W.; Noury, A.; Alonso-Ramos, C.; Hoang, H. C.; Serna- Otalvaro, S. F.; Le Roux, X.; Cassan, E.; Izard, N.; Vivien, L.; Sarti, F.; Torrini, U.; et al. (IEEE-NANO 2015 - 15th International Conference on Nanotechnology, 2015)
This paper reports on recent results on the integration of carbon nanotubes on the silicon photonic platform. Light coupling from carbon nanotubes in a fully integrated silicon resonator will be presented.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nanotubes; CMOS fabrication; light emission; ring resonator; silicon photonics